2022
DOI: 10.1177/03611981211070286
|View full text |Cite
|
Sign up to set email alerts
|

Velocity Obstacle-Based Collision Avoidance and Motion Planning Framework for Connected and Automated Vehicles

Abstract: This study proposes a novel collision avoidance and motion planning framework for connected and automated vehicles based on an improved velocity obstacle (VO) method. The controller framework consists of two parts, that is, collision avoidance method and motion planning algorithm. The VO algorithm is introduced to deduce the velocity conditions of a vehicle collision. A collision risk potential field (CRPF) is constructed to modify the collision area calculated by the VO algorithm. A vehicle dynamic model is p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…where d m,n (t ) represents the relative distance between the boundaries of HV and SV at time t. The minimum relative distance can be obtained by comparing all the relative distances between the HV and SV. The relative velocity ḋ m,n (t ) between boundaries of the HV and SV can be obtained by taking the time derivative of d m,n (t ) as shown in Equation (11).…”
Section: Definition Of Performance Metricsmentioning
confidence: 99%
See 1 more Smart Citation
“…where d m,n (t ) represents the relative distance between the boundaries of HV and SV at time t. The minimum relative distance can be obtained by comparing all the relative distances between the HV and SV. The relative velocity ḋ m,n (t ) between boundaries of the HV and SV can be obtained by taking the time derivative of d m,n (t ) as shown in Equation (11).…”
Section: Definition Of Performance Metricsmentioning
confidence: 99%
“…The results showed that the potential risk characteristics, such as properly controlled intersections and road obstacles, are considered important characteristics affecting road safety. In the study of risk calculation for autonomous vehicles [11], the risk between vehicles is computed using the collision risk potential field model, which modifies the collision area based on the velocity obstacle method.…”
Section: Introductionmentioning
confidence: 99%
“…In ref. [32], VO is applied to deduce the collision conditions in connected and automated vehicles. However, these VO-based methods require high computation costs in crowded environments [33].…”
Section: Related Workmentioning
confidence: 99%
“…The normal driving environment of the vehicle is often unknown, and the obstacles that appear must be discretized and polynomial curves are added to the artificial potential field to plan a path with the optimal curvature to ensure the vehicle travels [34,35]. In the speed control of the vehicle, the desired speed can be obtained by imitating the driver's behavior by adding an artificial potential field to the path planner [36][37][38]. When there is an obstacle in front of the road, the planner can control the vehicle to decelerate in time [39].…”
Section: Introductionmentioning
confidence: 99%